2009
DOI: 10.1017/cbo9780511609695
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Thermodynamics

Abstract: This textbook presents a uniquely integrated approach in linking both physics and chemistry to the study of atmospheric thermodynamics. The book explains the classical laws of thermodynamics, focuses on various fluid systems, and, recognising the increasing importance of chemistry in the meteorological and climate sciences, devotes a chapter to chemical thermodynamics which includes an overview of photochemistry. Although students are expected to have some background knowledge of calculus, general chemistry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Real data show that the slope coefficients α and β deviate from their theoretical values of α = 0.068 (CC relationship coefficient) and β = 0.5 (parcel-theory coefficient) due to different meteorological boundary conditions [20,24].…”
Section: Identifying the Effect Of Temperature On Deep Convective Stomentioning
confidence: 88%
See 4 more Smart Citations
“…Real data show that the slope coefficients α and β deviate from their theoretical values of α = 0.068 (CC relationship coefficient) and β = 0.5 (parcel-theory coefficient) due to different meteorological boundary conditions [20,24].…”
Section: Identifying the Effect Of Temperature On Deep Convective Stomentioning
confidence: 88%
“…Previous research by [24] and based on the CC relationship and idealized parcel theory suggested a relation between rainfall and both climatic variables of the type:…”
Section: Identifying the Effect Of Temperature On Deep Convective Stomentioning
confidence: 99%
See 3 more Smart Citations